AN ANALYSIS ON ADJECTIVE CLAUSE IN DANIEL DEFOES ROBINSON CRUSOE - Muhammad Ramadhan; Ni Made Widisanti S; Sari Rejeki (Journal Albion : Journal of English Literature, Language, and Culture, 2019)
Abstract This thesis is titled "An Analysis on Adjective Clause in Daniel Defoes Robinson Crusoe." This study aims to show the dominant function and type of adjective clause. In addition, this research is also conducted to show the fragmentary differences between Early Modern English and Modern English. The researcher used the adjective clause theory of Oshima and Hogue which included 6 functions and 2 types of adjective clause. The method used in this study is library qualitative or in other words library research.From this study, it can be concluded that 94 clauses data with functions and types of adjective clause were found and the dominant function of the adjective clause was relative pronoun as object 35 data equivalent to 37.23%. The difference in fragment between Early Modern English and Modern English is occured in the use of suffix st, -est, and t, the use of do auxiliaries, the use of pronoun thou, the use of the word will vs shall and the use of demonstrative pronoun.Keywords : adjective clause, functions and types of adjective clause.